"We definitely need an audience": experiences of Twitter, Twitter networks and tweet content in adults with severe communication disabilities who use augmentative and alternative communication (AAC). (August 2015) - Hemsley, Bronwyn; Dann, Stephen; Palmer, Stuart; Allan, Meredith; Balandin, Susan
Abstract Purpose: The aim of this study was to investigate the Twitter experiences of adults with severe communication disabilities who use augmentative and alternative communication (AAC) to inform Twitter training and further research on the use of Twitter in populations with communication disabilities. Method: This mixed methods research included five adults with severe communication disabilities who use AAC. It combined (a) quantitative analysis of Twitter networks and (b) manual coding of tweets with (c) narrative interviews with participants on their Twitter experiences and results. Results: The five participants who used AAC and Twitter were diverse in their patterns and experiences of using Twitter. Twitter networks reflected interaction with a close-knit network of people rather than with the broader publics on Twitter. Conversational, Broadcast and Pass Along tweets featured most prominently, with limited use of News or Social Presence tweets. Tweets appeared mostly within each participant's micro- or meso-structural layers of Twitter. Conclusions: People who use AAC report positive experiences in using Twitter. Obtaining help in Twitter, and engaging in hashtag communities facilitated higher frequency of tweets and establishment of Twitter networks. Results reflected an inter-connection of participant Twitter networks that might form part of a larger as yet unexplored emergent community of people who use AAC in Twitter. Implications for Rehabilitation Twitter can be used as an important vehicle for conversation and a forum for people with communication disabilities to exchange information and participate socially in online communities. It is important that information and resources relating to the effective use of Twitter for a range of purposes are made available to people with communication disabilities who wish to take up or maintain use of Twitter. People with communication disabilities might benefit from support in using Twitter to meet their goals relating to participation in online forums and information exchange. Practitioners need to consider how their own social media skills might impact on service delivery and supporting these goals.